ANALISA PERILAKU “POLITICAL FLAMING” DALAM KOLOM KOMENTAR PEMBACA PADA PEMBERITAAN TOKOH POLITIK - Melisa Indriana Putri (Jurnal Komunikasi dan Kajian Media, 2018)
Indonesia re-entered the new round of politics in 2018–2019. The vibrant political atmosphere is also reaching the public spaces, both in mass media and in online media. Although they often encounter differences due to the different political choices they face, audiences who have face-to-face discussions have the opportunity to clarify different conversational biases. However, many are discussing in the digital space, where it has the potential to cause a lot of message biases. The problem is political flaming often accompanies opinion bias. This study aims to find the characteristics of political flaming against Cak Imin since he runs as Vice President Jokowi unilaterally. Another goal is to see the attributes of the platform used in political flaming through content analysis approach. The results of this study show that political flaming against Cak Imin has a subtle tendency and jokes. The use of cultural elements is not intended as an expression of intolerance. Keywords: political flaming, reader comments, online media